Dampak Strategi Maritim Terhadap Peningkatan Keamanan Maritim Indonesia Terkait Ancaman IUU Fishing di Wilayah NKRI Tahun 2014-2017 - Hidayat, Muhammad Rifki (Global and Policy Journal of International Relations, 2019)
Since the 1990s, IUU Fishing has been a threat to Indonesian maritim security.Natuna Sea, Arafura Sea, and Sulu Sulawesi Seais vulnerable location which IUU Fishing happen. Not only defense function, but also IUU Fishing has become threat to public welfare. IUU Fishing threatening fishery industry that become source of employment and food stock in fishery sector. Therefore, Indonesia applies maritim strategy in the form of ship sinking policy and improve function of surveillance as a control in the maritim region. This research will explain how the impact ofthe application of ship sinking policy to enhancing maritim security related to the threat of IUU Fishing in the NKRI territory in 2014-2017.The application of maritim strategy has an impact on improving Indonesian maritim security. Improvement in maritim security is measured based on maritim security indicators. The maritim security indicators are measured based on 4 dimensions of the concept of maritim security,namely sea power, marine safety, blue economy, and human resilience. Keywords : IUU Fishing, Maritim Security, Indonesia, Maritim Strategy DOI : https://doi.org/10.33005/jgp.v7i01.1817